Nutracéuticos, alimentos funcionales y su producción - Cruzado, Martín (2012)
Nowadays, nutrition is not only based on what we cook, but also in what we take as supplements. Many products have invaded us: vitamins, aminoacids, vegetal extracts, omega-3, etc.  In this work we explain some important concepts such as nutraceuticals, functional and fortified foods, and also the way these products are made.